EKSTRAKURIKULER PRAMUKA TERINTEGRASI SIAGA BENCANA GEMPA BUMI TERHADAP KETERAMPILAN TANGGAP BENCANA SISWA SD - Puspadiningrum, Delvia; Winarni, Endang Widi; Hasnawati, Hasnawati (UNIB Press, 2017)
This study aims to determine the effect of extracurricular scouting integrated standby earthquake disaster response skill alert for elementary school students in the city of Bengkulu. This research is a quantitative research. The research design used is The Matching Only Pretest-posttest Control Group Design, the population in this study all the scout participants in SD Negeri Kota Bengkulu. The selected research sample is SD Negeri 02 Kota Bengkulu as Experiment and SD Negeri 19 Kota Bengkulu as the control. The research instruments used are observation sheets given through pretest (before activity) and posttest (after activity). Data of this research are analyzed by using descriptive and inferential analysis that is t-test. From the research results it is known that the average value of experimental group posttest is 80 control group equal to 57.2. The result of t-test with tcount is 9,785 and ttabel 2,306. So thitung>ttable, so it can be concluded that there is an extracurricular influence of integrated scouting education on earthquake disaster preparedness to disaster response preparedness skills of elementary school students in BengkuluCity.